Efektifitas Konseling Kelompok Melalui Teknik Restrukturisasi Kognitif Untuk Mengurangi Sikap Menarik Diri pada Santri Pondok Pesantren TIDAR Kota Magelang - Munawaroh, Munawaroh; Indiati, Indiati; Kurniati, Astiwi (Prosiding University Research Colloquium, 2022)
This research aims to test the effectiveness of group counseling through cognitive restructuring techniques to reduce the attitude of withdrawing students from the TIDAR Islamic Boarding School, Magelang City. The design of this research is one group pretest Posttest Design. The sample taken in this study were 7 students as the experimental group. The sample technique used was random sampling by lottery method. The method of collecting data is using a withdrawal attitude questionnaire. The data analysis method used is parametric analysis Paired sample t-test. The results of this study indicate that the Cognitive Restructuring Technique Group Counseling is effective for reducing withdrawal attitudes. This is evidenced by the results of the paired Sample t-test with a probability value of sig (2-tailed) 0,000 < 0.05. Based on the results of the analysis and discussion there are differences in scores the average withdrawal attitude questionnaire. The results of the decrease in pretest and posttest scores, the highest score was 24% and the lowest was 12%, the average score decreased was 17%. The significant decrease in pretest and posttest scores indicates that Cognitive Restructuring Technique Group Counseling is effective in reducing withdrawn attitudes in students.